DYNAMIC ASSESSMENT OF INTERNAL WATERS OF THE JIZZAKH REGION (Web of Teachers: Inderscience Research, 2025)
In this article, the role of the law of periodicity on the basis of the natural geographic conditions of Jizzakh region, interconnectedness and interconnectedness of geological and geographical features is indicated.